Hitting the mark: probing at the initiation site allows for accurate prediction of a thin shell's buckling load. (3rd April 2023) - Cuccia, Nicholas L.; Kumar Yadav, Kshitij; Serlin, Marec; Virot, Emmanuel; Gerasimidis, Simos; Rubinstein, Shmuel M.
Abstract : Geometric imperfections are understood to play an essential part in the buckling of a thin shell, but how multiple defects interact to control the onset of failure remains unclear. Here, we examine the failure of real cylindrical shells by experimentally poking soda cans with a large imparted dimple. By high-speed imaging of the can's surface, the initiation of buckling from axial loading is directly observed, revealing that larger dimples tend to set the initial buckling location. However, the influence of the shell's background geometric imperfections can still occasionally dominate, causing initiation to occur far from the dimple. In this situation, probing at the dimple leads to an over-prediction of the axial capacity. Using finite-element simulations, we understand our experimental results as a competition between the large dimple and the shell's inherent defect structure. In our simulations, we empirically observe a deformation-based criterion that connects the ideal poking location to the initiation site. This article is part of the theme issue 'Probing and dynamics of shock sensitive shells'.